Price transmission, domestic relative incentives and inter-sector resource flow analysis - Evious K. Zgovu (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2003)
This paper models the implications of partial pass-through of tariff/subsidy-inclusive border prices for the domestic relative incentive structure and inter-sector resource flow. The paper shows that partial pass-through reduces nominal protection, affects substitutability in the economy and ultimately the pattern of relative sectoral incentives. In general, the smaller the pass-through the smaller the lowering of pro-importables and anti-exportables incentive biases after tariff reforms. Consequently, commercial policy is unlikely to achieve full extent of inter-sector resource flows, at least in the short-term. Sluggish export supply response to tariff reforms in developing countries could be due to major pass-through problems.
Keywords: 330